2013
DOI: 10.1002/hep.26009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional identification of the likely causative variant for cholesterol gallstone disease at the ABCG5/8 lithogenic locus

Abstract: The sterolin locus ( ABCG5/ABCG8 ) confers susceptibility for cholesterol gallstone disease in humans. Both the responsible variant and the molecular mechanism causing an increased incidence of gallstones in these patients have as yet not been identified. Genetic mapping utilized patient samples from Germany (2,808 cases, 2,089 controls), Chile (680 cases, 442 controls), Denm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 41 publications
7
52
0
Order By: Relevance
“…Interestingly, the ABCG5/G8 locus has also long been implicated in the formation of cholesterol gallstones [10]. Recently, specific coding variants have been identified in genome-wide association studies that likely result in a gain-of-function of ABCG5/G8, supposedly translating into increased biliary cholesterol secretion [11]. Neither in animal experiments nor in human material has the functionality of ABCG5/G8, specifically in the gallbladder, been explored; although, derived from their function in liver and intestine increasing cholesterol secretion into bile would be expected.…”
mentioning
confidence: 99%
“…Interestingly, the ABCG5/G8 locus has also long been implicated in the formation of cholesterol gallstones [10]. Recently, specific coding variants have been identified in genome-wide association studies that likely result in a gain-of-function of ABCG5/G8, supposedly translating into increased biliary cholesterol secretion [11]. Neither in animal experiments nor in human material has the functionality of ABCG5/G8, specifically in the gallbladder, been explored; although, derived from their function in liver and intestine increasing cholesterol secretion into bile would be expected.…”
mentioning
confidence: 99%
“…2 Genetic and functional identification of the likely causative variant for cholesterol gallstone disease is at the ABCG5/8 lithogenic locus. 3 The prevalence of gallbladder stones is higher among patients with chronic kidney disease in Taiwan. 4 Susruta described jaundice called pittaash mari janya meaning a jaundice caused by stone in bile.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate genes tested in human cohorts include for example the apolipoproteins E (APOE) [58] and B (APOB) [59,60], cholesterol 7 α-hydroxylase [61,62], cholecystokinin receptor A (CCKAR) [63], the low density lipoprotein receptor related protein-associated protein (LRPAP1) [64] and the cholesterol ester transporting protein (CETP) [65]. Finally, genome-wide association analyses and functional studies have identified the p. D19H variant of the hepatic cholesterol hemitransporter (ABCG8) associated with susceptibility for human gallstones [55,66,67]. To our knowledge the only genome-wide association study (GWAS) of patients with gallbladder cancer published to date (https://www.ebi.ac.uk/gwas/) was conducted in a relatively small Japanese discovery cohort of 41 GC patients and 866 controls, and a subsequent validation cohort of 30 cases and 898 controls [68].…”
Section: Potential Susceptibility Genes For Gallbladder Cancermentioning
confidence: 99%